1st Plasma for Nanotechnology and Bioapplications Workshop Scientific Program & Book of Abstract - Kováčik, Dušan; Sihelník, Slavomír; Štěpánová, Vlasta; Krumpolec, Richard (Masaryk University Press, 2019)
The Book of Abstracts contains the contributions for presentations during the 1st Plasma for Nanotechnology and Bioapplications Workshop held on 8th - 10th December 2019 in University Centre in Telč. Workshop was attended by the researcher teams from Department of Physical Electronics, Faculty of Science, Masaryk University in Brno (CEPLANT), and Department of Experimental Physics, Faculty of Mathematics, Physics and Informatics, Comenius University in Bratislava. Within the workshop the contributions from the following five topics: Surface Modification; Flexible Electronics; Plasma Discharges and Sources; Bioapplications; and New Materials & New Challenges will be presented in the form of oral presentations.